Odpowiedzi

2010-02-18T15:55:51+01:00
3/8x(-0,9)x(-16/3)=1,8 do potęgi 2
5x(-0,25)x0,2x(-4)=1x do potęgi 2
(-2,5)x0,2x(-10)x2=10x do potęgi 3
(-6)x(-4/7)x2/5x(-7)x5/12=-307.2x do potęgi 3
(-1i1/2)x0,06x(-2/3)x100=6x do potęgi 3
Najlepsza Odpowiedź!
2010-02-18T16:00:09+01:00
3/8x(-0,9)x(-16/3)= ⅜ x (-¹⁶/₃) x (- ⁹/₁₀) = -2 x (- ⁹/₁₀) = ⁹/₅ = 1⅘

5x(-0,25)x0,2x( -4)= 5 x (-4) x (-¼) x (²/₁₀) = -20 x (-¹/₂₀) = 1

(-2,5)x0,2x(-10)x2= (-2½) x ²/₁₀ x (-10) x 2 = (-⁵/₂)x ²/₁₀ x -20 =
-½ x -20 = 10

(-6)x(-4/7)x2/5x(-7)x5/12= (-7) x (-⁴/₇) x ⅖ x ⁵/₁₂ x (-6) =
4 x ⅙ x (-6) = 4 x (-1) = -4

(-1i1/2)x0,06x(-2/3)x100= (-³/₂) x (-⅔) x (³/₅₀) x 100 =
⅗ x 6 = ¹⁸/₅ = 3 ⅗